Study of electrical properties of alg-pva-nh4no3 complexed polymer electrolyte films - N.M, Ghazali; Ahmad Salihin, Samsudin (2022)
In this work, the studies on electrical properties of bio-polymer blend electrolytes (BBEs)-based alginate-poly (vinyl alcohol) (Alg-PVA) blend complexed with various NH4NO3 salt weight percent was carried out and successfully prepared via solution casting method. Electrical impedance spectroscopy (EIS) was used to analyze the film’s conducting behavior, and it was found that both salt content and temperature improved the ionic conductivity of the BBEs system with the highest ionic conductivity reach at 5.20 × 10-4 S cm-1 for a sample containing with 35 wt.% of NH4NO3. The BBEs were found to follow the Arrhenius relation as a function of temperature. From the impedance analysis, the electrical properties of the BBEs system were examined using complex permittivity, ɛ* and complex electrical modulus, M* to further study the relation between the Alg-PVA bio-polymer blend with NH4NO3.